Body fat reserves and their relationship to ultrasound back fat measurements in Pelibuey ewes - Chay-Canul, Alfonso J.; Garcia-Herrera, Ricardo; Meza-Villalvazo, Victor M.; Gomez-Vazquez, Armando; Cruz-Hernandez, Aldenamar; Magaña-Monforte, Juan G.; Ku-Vera, Juan C. (Ecosistemas y Recursos Agropecuarios, 2016)
This study was conducted to evaluate body fat reserves (BFD) and their relationship to ultrasound back fat thickness (BFT) measurements in twenty Pelibuey ewes. The BFT was determined 24 h before slaughter using real-time ultrasound equipment with a 6/8 MHz probe. At slaughter, internal fat (TIF) was dissected and weighed. The carcasses were split into two halves, weighed and chilled (6◦C for 24 h). The left half-carcasses were completely dissected into muscle, bone and subcutaneous and intermuscular fat (carcass fat, TCF), and weighed separately. The r values for BFT and BFD ranged from 0.39 to 0.72. Regression equations between BFT and BFD had an R2 ranging from 0.15 to 0.52. Using BFT to predict BFD in Pelibuey ewes was poorly correlated.